Improved climate change cost assessments and socio-economic tipping points (Ökologisches Wirtschaften - Fachzeitschrift, 2022)
Economic costs of climate change have long been studied and various methods exist to assess the costs of climate protection and adaptation measures. But how can these costs be estimated on a regional level? And how does climate change affect regional economic systems?